India rising tales from a changing nation - Balch, Oliver (London Faber and Faber, 2012)
India is on the up. Historically derided as the lumbering elephant of Asia, this vast sub-continent has quickened its pace. The economy is booming. Tens of millions have been pulled out of poverty. Software and service companies abound. Millionaire entrepreneurs are springing up at every turn. Bollywood is going global and Indian expats are flooding back home. What's more, these changes are occurring within the world's largest democracy - a far cry from neighbouring China. But who and what lies behind India's apparent ascendency?
Includes index.
Keywords: India -Description and travel